RESPON SEISMIK STRUKTUR RANGKA DINDING PENGISI YANG DIMODEL DENGAN ELEMEN SHELL PENUH DAN PARSIAL - Putu Ratna Suryantini; M. Sukrawa; I. A. M Budiwati (JURNAL SPEKTRAN, 2017)
Abstract: Research on the seismic response of in-filled frame structure has been done with in-filled frame model as full and partial shell elements. The wall is considered active until the maximum load on the full shell models, while the partial shell model using the gradual load with the strength of the wall is considered inactive if the stress of the wall exceeded the wall strength The 4 storey hotel building with full wall in x-direction and wall with opening in y-direction were modeled in SAP 2000 as 3D infilled-frame using full and partial shell element. In Mxy models, both wall were included in the model, while in My models, only the wall in y-direction included. Therefore, 4 models were obtained, there are full shell model MxyShPn and MyShPn and partial shell model MyShPar and MyShPar. In addition, 2 diagonal strut models MxyS and MyS  and an open frame model MOF were made as comparison. Prior to model 3D structure, validation models were created using test result condited by other as reference. For that purphose 5 2D models were created there are open frame model MOF, single strut model MST, multiple strut model MSG, full shell model MShPn and  partial shell model MShPar. From validation models, it is apparent that the MxyShPar model mimic the behavior of tested structure better than the other models. From the 3D models analysis result show that the displacement in x-direction of MxyShPn, MxyShPar, MxyS were 89%, 85%, 84% smaller than those of MOF, respectively inclusion of wall in the models, also reduce the internal forces and reduse the natural period of the sctructure.